Sistem Informasi Pendaftaran Siswa Baru Berbasis Web Pada Smp Islam 1 Kota Ternate - Muhammad Aditya Septian Sundah (Manajemen Informatika, Akademi Ilmu Komputer Ternate, 2023)
New student registration activities are routine activities carried out by schools in each new academic year. Registration is the first step in entering or joining an agency. In addition, registration is an administrative process that occurs every year for the selection of new students based on academic grades in order to continue their education at a higher level. The system that is still used at Smp Islam 1 City Of Ternate is currently still in the process of accepting new students, it is still done manually, namely by filling out the form using the sheet provided by the committee, because using handwriting will allow the committee to have difficulty reading the form that has been filled in by the candidate. student. Therefore, to simplify the process of accepting new students, it is necessary to develop an online new student registration system, with the development of this system it will simplify the registration process, the administrative data collection process is easier, faster and more efficient in terms of time, place, cost and energy. Designing a web-based new student registration information system at Smp Islam 1 City Of Ternate, the programming languages ​​used are PHP, HTML, and CSS programming languages. As for the data management using MySQL in the XAMPP tool. With this application, the registration process for prospective new students will be easier and faster. The fast registration process will make parents and prospective new students more comfortable in registering.